Vulnerability Assessment of Slums – A Tool for Planning - Singh, Abha Lakshmi; Kaish, Mohd. (National Geographical Journal of India, 2022)
The study assesses the vulnerability of slums in Aligarh city, a medium sized city of North India. Information regarding vulnerable conditions were collected with the help of city/ slum surveys and questionnaire interviews. A total of 77 slum spots (having 5 and > 5 households) located within the city municipal limits were identified. Five slum clusters were identified for indepth assessment. About 13 criteria were selected for assessing the vulnerability. Individual and cumulative scores showed the differential vulnerability in the slum clusters/zones, which were further categorized under three, highly vulnerable (Zone 5-Bihari Nagar area, Zone 4 Shahjamal area), moderately vulnerable (Zone 3-Kathpula area, Zone 2-Dodhpur area) and less vulnerable (Zone 1 - University area) slum zones for the purpose of planning. The study indicates that slum formation will continue and there is need for improving the condition of slums and providing basic facilities like housing, water and sanitation.